2013
DOI: 10.3109/03008207.2012.762360
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sheep Chondrocytes to Changes in Substrate Stiffness from 2 to 20 Pa: Effect of Cell Passaging

Abstract: Chondrocytes respond differently according to the stiffness of the substrate. This response depends greatly on the oxygen environment and on whether the chondrocyte is embedded or grown onto the hydrogel, since mechanosensing capacity was not lost with cell expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…They noted that neurogenic differentiation was optimal at a stiffness of 0.1-1 kPa, myogenic differentiation at 8-17 kPa and osteogenic differentiation at 25-40 kPa. Several subsequent studies have shown how substrate stiffness affects several different cell types, including neuronal cells [134,135], chondrocytes [136], cardiomyocytes [137,138], dermal fibroblasts [139] and limbal stem cells [140]. Recently, Trappmann et al [141] suggested that substrates of different stiffness have differing protein anchorage densities and configurations that regulate stem cell fate through the mechanical feedback of cells attached to anchored proteins [141].…”
Section: Influence Of the Hydrogel On Cell Behaviourmentioning
confidence: 99%
“…They noted that neurogenic differentiation was optimal at a stiffness of 0.1-1 kPa, myogenic differentiation at 8-17 kPa and osteogenic differentiation at 25-40 kPa. Several subsequent studies have shown how substrate stiffness affects several different cell types, including neuronal cells [134,135], chondrocytes [136], cardiomyocytes [137,138], dermal fibroblasts [139] and limbal stem cells [140]. Recently, Trappmann et al [141] suggested that substrates of different stiffness have differing protein anchorage densities and configurations that regulate stem cell fate through the mechanical feedback of cells attached to anchored proteins [141].…”
Section: Influence Of the Hydrogel On Cell Behaviourmentioning
confidence: 99%
“…HIF-1␣ also acts as a central regulator of collagen production that allows chondrocytes to maintain their function as professional secretory cells in the hypoxic growth plate [27,28]. Hypoxia and HIF-1␣ not only induce the expression of SOX9, COL2A1, and aggrecan [29], but they simultaneously inhibit the expression of COL1A1, COL1A2, and COL3A1 [30]. HIF-1␣ is a survival factor for hypoxic chondrocytes [31], and it also negatively regulates cell proliferation [32].…”
Section: Hif-1␣ In Cartilage and Oamentioning
confidence: 99%
“…In the hypoxia growth plate, HIF-1α maintains chondrocytes function as professional secretory cells by regulating collagen production [5]. HIF-1α not only inhibits the expression of COL1A1, COL1A2 and COL3A1 [6] but also simultaneously induces the expression of SOX9, COL2A1 and aggrecan [7]. HIF-1α inhibits cell proliferation [8] and is a survival factor for hypoxic chondrocytes [9].…”
Section: Introductionmentioning
confidence: 99%